Transgressão, direitos e serviço social - Azevedo, Isabela Sarmet de (2006)
The main subject of this thesis is transgression. We would like it to be taken here as an attitude or behavior of indignation, of non-submission, as a refusal to what was established when it hinders human fulfillment, freedom, democracy, that is, the values that are inherent to any social being. Taking dialectical and historical materialism as a reference, it s our aim treating trangression as a culturalhistorical category created in man s life, at specific dimensions and also thought by them theoretically. In this sense, in our work, it has the form of disobedience, emphasizing its historical character in the political and ethical fields. Although disobedience cannot be considered revolutionary from marxist and revolutionary socialist movement s points of view, it is today found in movements that resist the capitalist order and fight against neoliberal globalization. While some of these movements are known by their lack of previous organization and by generating actions that might or not have a political continuity, others like the World Social Forum, look for a material basis to build another possible world . These movements show that besides resisting, it s necessary to create collective alternative policies. In our analysis we consider that, professionally, we could take the transgression to the institutional rules not as a political principle, but as a reaction to some given situations where institutional rules or some institution members behavior prevent the rights from happening. Here we find transgressions, punishments and protections of some Social Work professionals who sought the rights fulfillment in our society